Do Domestic Investors Have an Information Advantage? Evidence from Indonesia - DVOŘÁK, TOMÁŠ (Journal of Finance, 2005)
ABSTRACT Using transaction data from Indonesia, this paper shows that domestic investors have higher profits than foreign investors. In addition, clients of global brokerages have higher long‐term and smaller medium (intramonth) and short (intraday) term profits than clients of local brokerages. This suggests that clients of local brokerages have a short‐lived information advantage, but that clients of global brokerages are better at picking long‐term winners. Finally, domestic clients of global brokerages have higher profits than foreign clients of global brokerages, suggesting that the combination of local information and global expertise leads to higher profits.